Correlation between Human Papillomavirus Codetection Profiles and Cervical Intraepithelial Neoplasia in Japanese Women - Okayama, Kaori (Microorganisms, 2020)
Human papillomavirus (HPV) infection is thought to be strongly associated with the precarcinomatous state cervical intraepithelial neoplasia (CIN) and cervical carcinoma. To accurately assess the correlation between HPV detection profiles and CIN, the uniplex E6/E7 polymerase chain reaction (PCR) method was used. We detected HPV (37 genotypes) in 267 CIN cases. The detection of a single high-risk HPV genotype occurred in 69.7% of CIN1 and worse than CIN1 (CIN1+) cases whereas other types were detected in 11.6% of cases. Codetection of high-risk HPV genotypes occurred in 4.9% of CIN1+ cases. The high-risk genotype HPV16 was the most frequently detected genotype in CIN1+ lesions; the genotype HPV34 (not a high-risk type) was detected in some CIN3 cases. Furthermore, HPV codetection may not be associated with CIN grades. These results suggest that various HPV genotypes are associated with CIN across all analyzed cases.